Eco-Innovation Adoption in Emerging Markets: Analyzing Managerial and Environmental Factors in Indonesian SMEs - Fansuri Munawar; Keni Kaniawati; Rini Handayani; Andhi Sukma; Aditya Yudanegara; Sri Wiludjeng SP (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — This study examines the influence of managerial and environmental factors on the adoption of eco-innovation practices to improve business sustainability in small manufacturing firms.Method — The research employs a quantitative approach, gathering primary data from 110 owners and managers of small manufacturing firms in Bandung, Indonesia. Structural Equation Modeling (SEM) is utilized to analyze the relationships between managerial and environmental drivers, eco-innovation practices, and business sustainability. The data was analyzed using the Partial Least Squares (PLS) method via SmartPLS 3.0 software.Result — The study's findings demonstrate that both managerial drivers (such as eco-commitment, eco-efficiency, and eco-capability) and environmental drivers (including eco-consumer demand, eco-regulation, and eco-competition) have a significant positive impact on the adoption of eco-innovation practices. These eco-innovation practices, in turn, significantly contribute to enhancing business sustainability. This underscores the importance of integrating sustainable practices into business operations and proactively responding to environmental pressures to achieve long-term competitive advantage.Novelty — This research offers new insights by focusing on small manufacturing firms in an emerging market—a context that has been relatively underexplored in existing literature. Unlike previous studies that mainly target large enterprises or developed markets, this study highlights the critical role of eco-innovation in promoting sustainability within small firms in Indonesia. Moreover, it distinguishes the unique impacts of both managerial and environmental drivers, providing a more comprehensive understanding of the factors that motivate the adoption of eco-innovation practices in small enterprises.